1980
DOI: 10.1515/znb-1980-0415
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Riboflavin. Enzymatic Deamination of 2,5-Diamino-6-hydroxy-4-ribitylaminopyrimidine-5′-phosphate

Abstract: Cell extracts of Saccharomyces cerevisiae and Candida guilliermondii catalyze the hydrolytic deamination in position 2 of 2,5-diamino-6-hydroxy-4-ribitylaminopvrimidine 5′-phosphate. The deaminase activity is absent in rib 2 mutants of S. cerevisiae. These findings confirm the biosynthetic pathway proposed earlier on the basis of metabolic and genetic studies [2].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Early studies with the yeast Saccharomyces cerevisiae showed that the reduction of the side chain precedes the deamination of the ring, and 2,5-diamino-6-ribitylamino-4(3H)-pyrimidinone 5Ј-phosphate (compound 4) was proposed as an intermediate (18). This sequence of reactions was later confirmed by enzymatic in vitro studies with Ashbya gossypii and S. cerevisiae (10,11,17).…”
mentioning
confidence: 71%
“…Early studies with the yeast Saccharomyces cerevisiae showed that the reduction of the side chain precedes the deamination of the ring, and 2,5-diamino-6-ribitylamino-4(3H)-pyrimidinone 5Ј-phosphate (compound 4) was proposed as an intermediate (18). This sequence of reactions was later confirmed by enzymatic in vitro studies with Ashbya gossypii and S. cerevisiae (10,11,17).…”
mentioning
confidence: 71%
“…10,11 This sequence of reactions was later confirmed by enzymatic in vitro studies with Ashbya gossypii and Saccharomyces cerevisiae. [12][13][14] On the other hand, the deamination step (Figure 1, d) was shown to precede the side-chain reduction (Figure 1, e) in eubacteria 15 and in higher plants. 16 Early studies showed the basic pathway of riboflavin biosynthesis in Archaea to be similar to that of Eubacteria and fungi by in vivo studies with 13 C-labeled precursors.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] On the other hand, the deamination step (Figure 1, d) was shown to precede the side-chain reduction (Figure 1, e) in eubacteria 15 and in higher plants. 16 Early studies showed the basic pathway of riboflavin biosynthesis in Archaea to be similar to that of Eubacteria and fungi by in vivo studies with 13 C-labeled precursors. 17 5-Amino-6-ribitylamino-2,4(1H,3H)-pyrimidinedione 5′-phosphate (6) needs to be dephosphorylated prior to the enzymatic formation of 6,7-dimethyl-8-ribityllumazine (8), but the hypothetical phosphatase has not yet been described.…”
Section: Introductionmentioning
confidence: 99%
“…2) (15). Hydrolytic cleavage of the 2-amino group and reduction of the ribose side chain yield 5 -amino-6-ribitylamino-2,4(1H,3H) -pyrimidinedione 5-phosphate (compound 5) (2,18,22). Removal of the phosphate group yields 5-amino-6-ribitylamino-2,4(1H,3H)-pyrimidinedione (compound 6), which is condensed with 3,4-dihydroxy-2-butanone 4-phosphate (compound 7) under formation of 6,7-dimethyl-8-ribityllumazine (compound 8).…”
Section: Resultsmentioning
confidence: 99%